Multicenter Evaluation of Nine Commercial Kits for the Quantitation of Anticardiolipin Antibodies - Reber, G; Arvieux, J; Comby, E; Degenne, D; de Moerloose, P; Sanmarco, M; Potron, G; On behalf of the working group on Methodologies in Haemostasis from the GEHT (Groupe d’Etudes sur I’Hémostase et la Thrombose), France (Thrombosis and Haemostasis, 1995)
The performances of nine commercial kits and an in-house method (HM) for the quantitation of anticardiolipin antibodies (ACA) have been evaluated in a multicenter study. Ninety control and patient samples and six standards from Louisville University were run with kits and with the HM. Marked differences in positivity rate between kits were observed, ranging from 31 to 60% for IgG and 6 to 50% for IgM. Concordance between kits occurred in 59 and 51% of samples for IgG and IgM respectively. Concordance coefficients (kappa) ranged from 0.13 to 0.92. Slopes of regression lines between the declared units of Louisville standards and the units measured from the calibrators of the kits showed great diversity and ranged from 0.159 to 0.931 for IgG and from 0.236 to 0.836 for IgM. The β2-glycoprotein I (β2-GPI) content of the dilution buffers and the wells supplied with the kits revealed noticeable differences. However samples containing anti-(β2-GPI antibodies were classified similarly by all but one kit. In contrast the ability to measure samples devoid of anti-β2-GPI antibodies differed markedly between the kits.This study shows that differences in positivity rates between the commercial kits may contribute to the differences in ACA prevalence rate found in the literature. The choice of cut-off levels may partly explain the moderate concordance between the kits. In addition some samples behave very differently depending on the kits. In spite of the expression of results in PL units, standardization of ACA assays has not been achieved.